Single nucleotide polymorphisms in the Trx2/TXNIP and TrxR2 genes of the mitochondrial thioredoxin antioxidant system and the risk of diabetic retinopathy in patients with Type 2 diabetes mellitus - Ramus, Sara Mankoc; Cilensek, Ines; Petrovic, Mojca Globocnik; Soucek, Miroslav; Kruzliak, Peter; Petrovic, Daniel (Journal of diabetes and its complications, 2016)
BACKGROUND: Oxidative stress plays an important role in the pathogenesis of diabetes and its complications. The aim of this study was to examine the possible association between seven single nucleotide polymorphisms (SNPs) of the Trx2/TXNIP and TrxR2 genes encoding proteins involved in the thioredoxin antioxidant defence system and the risk of diabetic retinopthy (DR). DESIGN: Cross-sectional case-control study. PARTICIPANTS: A total of 802 Slovenian patients with Type 2 diabetes mellitus; 277 patients with DR and 525 with no DR were enrolled. METHODS: Patients genotypes of the SNPs; including rs8140110, rs7211, rs7212, rs4755, rs1548357, rs4485648 and rs5748469 were determined by the competitive allele specific PCR method. MAIN OUTCOME MEASURES: Each genotype of examined SNPs was regressed in a logistic model, assuming the co-dominant, dominant and the recessive models of inheritance with covariates of duration of diabetes, HbA1c, insulin therapy, total cholesterol and LDL cholesterol levels. RESULTS: In the present study, for the first time we identified an association between the rs4485648 polymorphism of the TrxR2 gene and DR in Caucasians with Type 2 DM. The estimated ORs of adjusted logistic regression models were found to be as follows: 4.4 for CT heterozygotes, 4.3 for TT homozygotes (co-dominant genetic model) and 4.4 for CT+TT genotypes (dominant genetic model). CONCLUSIONS: In our case-control study we were not able to demonstrate any association between rs8140110, rs7211, rs7212, rs4755, rs1548357, and rs5748469 and DR, however, our findings provide evidence that the rs4485648 polymorphism of the TrxR2 gene might exert an independent effect on the development of DR.
Keywords: Cross-Sectional Studies; Mitochondria; Thioredoxins; genetické asociační studie; Male; Genetic Predisposition to Disease; Risk Factors; Oxidative stress; genetická predispozice k nemoci; Genetic Association Studies; Diabetic Retinopathy; Aged; Case-Control Studies; Diabetes Mellitus, Type 2; mužské pohlaví; senioři; jednonukleotidový polymorfismus; thioredoxiny; Thioredoxin Reductase 2; thioredoxinreduktasa 2; mitochondriální proteiny; diabetes mellitus 2. typu; diabetická retinopatie; Carrier Proteins; Mitochondrial Proteins; Thioredoxin antioxidant system; Polymorphism, Single Nucleotide; lidé; ženské pohlaví; studie případů a kontrol; Humans; metabolické sítě a dráhy; rizikové faktory; průřezové studie; Diabetic retinopathy; Single nucleotide polymorphism; Type 2 diabetes mellitus; Female; lidé středního věku; Metabolic Networks and Pathways; transportní proteiny; mitochondrie; Middle Aged